Step-structured copper-molybdenum-copper-copper composite material and preparation method thereof
By laser welding of copper-molybdenum copper material with an oxygen-free copper inverted U-shaped structure and using pulsed laser forging to remove internal stress, the problem of limited step height difference accuracy of copper-molybdenum copper structural parts in the prior art is solved, and precision processing and efficient mass production of step structures are achieved.
Patent Information
- Application Number
- CN202510089527.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-05-02
AI Technical Summary
When preparing copper-molybdenum copper structural parts with precision step size requirements, the prior art is limited by the material stress and strain difference, resulting in limited accuracy of step height difference, which makes it easy to cause structural deformity and dimensional failure.
Copper-molybdenum copper material is used as the bottom straight member, combined with the inverted U-shaped structure of oxygen-free copper, laser welding is performed, and the internal stress of the weld is removed through pulsed laser forging, and finally mechanical cutting of the unit is performed to prepare step-shaped copper-molybdenum copper-copper composite material.
It realizes precision processing of step structure, eliminates material bending and fracture defects, improves the accuracy of step height difference, and has a simple process and low manufacturing cost, making it suitable for mass production.
Smart Images

Figure CN119913441A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of heterogeneous metal-based composite materials for module packaging, and in particular to a step-structured copper-molybdenum-copper-copper composite material and a preparation method thereof. Background Art
[0002] Power semiconductor devices achieve chip-to-external electrical connection through packaging. According to Moore's Law, the chip area continues to decrease, and the bonding material has also evolved from gold wire bonding in 2001 to aluminum wire (ribbon) bonding in 2006, copper wire bonding in 2011, and copper strip bonding in 2016. In response to the performance improvement drive of high-power devices, the greater the power, the higher the requirements. In order to obtain smaller parasitic inductance, unique packaging resistance value, higher current, better thermal conductivity, and higher power reliability, copper-molybdenum-copper strips are proposed as a new generation of new bonding materials.
[0003] At present, the main production method of molybdenum-copper-copper materials is the rolling composite method, which prepares straight copper-molybdenum-copper composite materials, and then further processes step structures with a certain curvature, size and shape according to the binding requirements. In particular, the step height difference is a key dimension that directly affects the welding of the chip and the substrate, otherwise it will cause defects such as cold welding and affect the reliability of the package.
[0004] Copper-molybdenum-copper structural parts with precise step size requirements prepared by existing technologies are limited by the stress-strain differences of different materials. The use of molds for one-time molding often greatly restricts the accuracy of step height differences due to non-cooperative deformation of materials, especially for high aspect ratio structural parts, and may even lead to structural deformity and dimensional failure.
[0005] The present invention designs a new material structure of a metal strip, wherein the straight component that contacts the solder at the bottom is made of copper-molybdenum-copper material, and the top arched structure material is made of oxygen-free copper. The contact interface is then laser welded, and the high-temperature cladding thermal stress is removed by laser forging, and finally the unit mechanical cutting is performed. The present invention does not require the bending of copper-molybdenum-copper materials, and eliminates the bending and fracture defects caused by the different mechanical stress properties of copper-molybdenum-copper materials. By laser welding the straight copper-molybdenum-copper material with the oxygen-free copper material on the set mold structure, the dimensional deviation such as the step height is solved, and the precision processing requirements of the step size are realized. Both the copper-molybdenum-copper material and the oxygen-free copper can be processed using large pieces of material. The present invention has the advantages of simple processing equipment, low manufacturing cost, high processing efficiency, and high dimensional accuracy, and can be promoted and applied in production. Summary of the invention
[0006] The purpose of the present invention is to provide a step-structured copper-molybdenum-copper-copper composite material and a preparation method thereof based on the above technical problems.
[0007] In order to achieve the above object, a first aspect of the present invention provides a method for preparing a step-structured copper-molybdenum-copper-copper composite material, the method comprising the following steps:
[0008] (1) using a flat structured molybdenum material as a core material, and cladding copper plates I and II on both sides of the core material, respectively, to obtain an intermediate material having a structure of copper plate I-core material-copper plate II from top to bottom, and performing rolling treatment, first flattening treatment, and first cutting treatment on the intermediate material in sequence, to obtain an intermediate (2) having a thickness of 0.01 to 1 mm, a length of 5 to 80 mm, a width of 2 to 40 mm, and a thickness ratio of copper, molybdenum, and copper of 1:(1 to 7):1;
[0009] (2) placing the oxygen-free copper sheet in a mold and sequentially performing a second flattening process, a second cutting process, and a bending process to obtain an inverted U-shaped copper sheet (1);
[0010] The surfaces and butt joint surfaces of the intermediate (2) and the inverted U-shaped structure copper sheet (1) are mechanically polished step by step using 100#, 200#, 400#, 800# and 1000# sandpapers, and then ultrasonically cleaned in ethanol for 10 to 20 minutes, vacuum dried for 10 to 30 minutes, and then the two are placed side by side on a welding table, and the positions of the two are adjusted so that the butt joint surfaces of the two are in close contact, and the two interface materials are welded using a continuous laser (3), and after the metal in the molten pool (5) solidifies, the weld surface is forged using a pulsed laser (4), and then in-situ heat treatment is performed to obtain a weldment;
[0011] (3) Mechanically dividing the weldment into units to obtain a copper-molybdenum-copper-copper composite material with a stepped structure.
[0012] Preferably, in step (1), the rolling process is to thin the thickness of the intermediate material in multiple passes, and the first pass is to thin the intermediate material to 50% of the initial thickness, the second pass is to thin the intermediate material to 30% of the initial thickness, the third pass is to thin the intermediate material to 20% of the initial thickness, and the fourth pass is to thin the intermediate material to 10% of the initial thickness, until the thickness is thinned to 0.01-1 mm, and the rolling process is terminated; annealing heat treatment is required each time the thickness is thinned.
[0013] Preferably, in step (1), the conditions for reducing the thickness of the intermediate material in multiple passes meet the following conditions: temperature is 550-590° C., and time is 0.5-2.5 h.
[0014] Further preferably, in step (1), the conditions of the annealing heat treatment meet the following requirements: temperature is 650-850° C., and time is 0.5-2.5 h.
[0015] More preferably, in step (2), the welding process conditions meet the following conditions: the power of the continuous laser (3) is 2000-6000 W, the welding rate is 10-30 mm / s, the shielding gas is argon, and the flow rate of the shielding gas is 10-25 L / min.
[0016] Preferably, in step (2), the forging treatment uses a pulse spot radius of 0.2 to 0.4 mm, and the forging treatment is to start from the beginning of the weld and move horizontally along the width direction of the weld to the end of the weld, completing one cycle, and repeating three times; and the conditions for the forging treatment meet: the power density of the pulse laser (4) is 0.6 to 1.2 GW / cm 2 , the pulse width is 10 to 30 ns, the frequency is 1 to 10 kHz, the forging rate of the pulse laser (4) is 5 to 20 mm / s, the shielding gas is argon, and the shielding gas flow rate is 10 to 25 L / min.
[0017] Preferably, in step (2), the in-situ heat treatment conditions meet the following requirements: temperature is 700° C. to 850° C., and holding time is 30 min to 60 min.
[0018] Further preferably, in step (1) and step (2), the first leveling treatment and the second leveling treatment are performed by using a high-precision leveling machine at room temperature for 3 to 5 times to ensure that the flatness is ≤0.02 mm.
[0019] Preferably, in step (1) or step (2), the first cutting process and the second cutting process are to cut the material using a wire cutting machine or a high-precision cutting machine to ensure a dimensional tolerance of ±0.01 mm.
[0020] Preferably, in step (2), the bending process is performed by using a high-strength steel concave-convex mold, the flat plate material to be bent is laid flat in the mold groove for positioning, the upper mold is covered, the operation is started on a punch press, the pressurization pressure is 0.1 to 3 MPa, and then the mold is removed to complete the bending.
[0021] The second aspect of the present invention provides a step-structured copper-molybdenum-copper-copper composite material prepared by the method described in the first aspect of the present invention, wherein the step-structured copper-molybdenum-copper-copper composite material has a thickness of 0.02 to 0.08, a width of 2 to 5 mm, and a step height of 0.1 to 0.55 mm.
[0022] The method provided by the present invention also has at least the following beneficial effects:
[0023] In view of the product failure problems such as warping deformation and large dimensional fluctuation in the existing complex molybdenum-copper-copper structural parts preparation methods, the present invention uses copper with high flexibility and high thermal conductivity as the bending part, combines the bottom direct solder and copper-molybdenum-copper composite material with low thermal expansion coefficient as a new structure, realizes the cladding combination of dissimilar interface materials through laser welding method, releases internal stress by pulse laser shock method on the weld, and improves the bending strength and reliability of the material structure after welding. The present invention can efficiently, mass-produce and continuously prepare precision copper-molybdenum-copper / copper strips with step structures, with high reliability, simple process and high yield rate, and is worthy of production and promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of preparing a copper-molybdenum-copper-copper composite material with a step structure according to Example 1 of the present invention;
[0025] Figure 2 It is a schematic diagram of the welding process and forging process in step (2) of Example 1 of the present invention.
[0026] Description of Reference Numerals
[0027] 1. Inverted U-shaped copper sheet 2. Intermediate
[0028] 3. Continuous laser 4. Pulse laser
[0029] 5. Molten pool DETAILED DESCRIPTION
[0030] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0031] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the raw materials are all commercially available.
[0032] In the following examples, unless otherwise specified, the normal temperature is 25±2°C.
[0033] Example 1
[0034] This example is used to combine Figure 1 A method for preparing a step-structured copper-molybdenum-copper-copper composite material is provided, and the method comprises the following steps:
[0035] (1) A flat structured molybdenum material with a size of 200×80×2.0 mm is used as a core material, and copper plates I and II with a size of 200×80×2.0 mm are respectively covered on both sides of the core material to obtain an intermediate material with a structure of copper plate I-core material-copper plate II from top to bottom, and the intermediate material is subjected to rolling treatment, first flattening treatment, and first cutting treatment in sequence to obtain a composite material with a thickness of 1 mm, a length of 80 mm, a width of 40 mm, and a thickness ratio of copper, molybdenum, and copper of 1:4:1, which is recorded as intermediate 2;
[0036] The rolling process is to thin the thickness of the intermediate material in multiple passes, and the first pass is to thin the intermediate material to 50% of the initial thickness of the intermediate material, the second pass is to thin the intermediate material to 30% of the initial thickness of the intermediate material, the third pass is to thin the intermediate material to 20% of the initial thickness of the intermediate material, and the fourth pass is to thin the intermediate material to 10% of the initial thickness, until the thickness is thinned to 1mm, that is, the rolling process is terminated; annealing heat treatment is required for each thickness thinning; wherein, the conditions for thinning the thickness of the intermediate material in multiple passes meet the following conditions: temperature is 550-590°C, time is 0.5-2.5h; the conditions for annealing heat treatment meet the following conditions: temperature is 650-850°C, time is 0.5-2.5h;
[0037] The first leveling process is to use a high-precision leveling machine to level three times at room temperature to ensure that the flatness is ≤0.02mm; the first cutting process is to first use a high-precision shearing machine to cut it into several sizes of 80×60mm, and then use a wire cutting machine to accurately divide it into small units A with a size of 2.52×3.2mm and small units B with a size of 3.5×3.2mm, ensuring that the length and width tolerance is ±0.01mm.
[0038] (2) An oxygen-free copper sheet with a thickness of 1 mm, a length of 300 mm, and a width of 80 mm is placed in a mold and subjected to a second leveling treatment, a second cutting treatment, and a bending treatment in sequence to obtain an inverted U-shaped copper sheet 1; the surfaces and the butt joint surfaces of the intermediate 2 and the inverted U-shaped copper sheet 1 are mechanically polished step by step with 100#, 200#, 400#, 800#, and 1000# sandpapers respectively, and then ultrasonically cleaned in ethanol for 15 min, vacuum dried at 80° C. for 15 min, and then the two are placed side by side on a welding table, and the positions of the two are adjusted so that the butt joint surfaces of the two are in close contact, and continuous laser 3 is used to weld the two interface materials (such as Figure 2 As shown), after the molten pool 5 metal solidifies, the pulse laser 4 is used to forge the weld surface (as shown Figure 2 As shown), and then in-situ heat treatment is performed to obtain a weldment;
[0039] The second leveling treatment is to use a high-precision leveling machine to level twice at room temperature to ensure that the flatness is ≤0.02mm;
[0040] The second cutting process is to first cut into 80×60 mm pieces using a high-precision shearing machine, and then use a wire cutting machine to precisely cut into small units C with a size of 6.15×3.2 mm, ensuring that the length and width tolerance is ±0.01 mm;
[0041] The bending process uses a high-strength steel concave-convex mold, and the small unit C of the flat material to be bent is flatly laid in the mold groove for positioning, and the upper mold is covered, and the operation is started on the punch press, the pressure is 0.5MPa, and then the mold is withdrawn, and the bending is completed;
[0042] The welding process conditions are as follows: the power of the continuous laser 3 is 2000W, the welding rate is 20mm / s, the shielding gas is argon, and the flow rate of the shielding gas is 25L / min;
[0043] The forging process uses a pulse spot radius of 0.2 mm, and the forging process is to start from the beginning of the weld and move horizontally along the width direction of the weld to the end of the weld, completing a cycle, and repeating three times; and the conditions of the forging process meet: the power density of the pulse laser 4 is 1.2 GW / cm 2 , the pulse width is 15ns, the frequency is 5kHz, the forging rate of the pulse laser 4 is 10mm / s, the shielding gas is argon, and the shielding gas flow rate is 25L / min;
[0044] The in-situ heat treatment conditions meet the following requirements: temperature is 700°C and holding time is 30 minutes. This treatment is a treatment measure applied after welding and forging to reduce the yield limit of the material under high temperature conditions, reduce the local internal stress of the material by generating plastic flow, gradually reduce the elastic deformation, and gradually increase the plastic deformation to relieve the stress.
[0045] (3) The weldment is mechanically divided into units by cutting with a tungsten carbide tool to obtain a step-structured copper-molybdenum-copper-copper composite material with a width of 3.2 mm and a step height of 0.5±0.01 mm; wherein, in the step-structured copper-molybdenum-copper-copper composite material, the tensile strength of the weld joint along the rolling direction of the base material is 600 MPa.
[0046] Example 2
[0047] This example is carried out according to the method of Example 1, except that in step (2), the welding process conditions meet the following conditions: the power of the continuous laser 3 is 6000 W, the welding rate is 10 mm / s, the shielding gas is argon, and the flow rate of the shielding gas is 20 L / min;
[0048] The conditions for the forging treatment are as follows: the power density of the pulsed laser 4 is 1.0 GW / cm 2, the pulse width is 10ns, the frequency is 1kHz, the forging rate of the pulse laser 4 is 5mm / s, the shielding gas is argon, and the shielding gas flow rate is 10L / min, and the remaining steps and parameters are the same as in Example 1.
[0049] Among them, a step-structured copper-molybdenum-copper-copper composite material with a width of 3.8 mm and a step height of 0.45 mm was obtained; wherein, in the step-structured copper-molybdenum-copper-copper composite material, the tensile strength of the welded joint along the rolling direction of the base material was 592 MPa.
[0050] Example 3
[0051] This example is carried out according to the method of Example 1, except that in step (2), the welding process conditions meet the following conditions: the power of the continuous laser 3 is 4000 W, the welding rate is 30 mm / s, the shielding gas is argon, and the flow rate of the shielding gas is 10 L / min;
[0052] The conditions for the forging treatment are as follows: the power density of the pulsed laser 4 is 0.6 GW / cm 2 , the pulse width is 30ns, the frequency is 20kHz, the forging rate of the pulse laser 4 is 20mm / s, the shielding gas is argon, and the shielding gas flow rate is 21L / min, and the remaining steps and parameters are the same as in Example 1.
[0053] Among them, a step-structured copper-molybdenum-copper-copper composite material with a width of 3.5 mm and a step height of 0.55 mm was obtained; wherein, in the step-structured copper-molybdenum-copper-copper composite material, the tensile strength of the welded joint along the rolling direction of the base material was 595 MPa.
[0054] Comparative Example 1
[0055] This example is carried out according to the method of Example 1, except that in step (1), in the first flattening process, it is divided into small units A with a size of 12.17×3.2 mm, and bent into workpieces. The remaining steps and parameters are the same as in Example 1.
[0056] Among them, a step-structured copper-molybdenum-copper-copper composite material with a width of 3.2 mm and a step height of 0.45 mm was obtained; wherein, in the step-structured copper-molybdenum-copper-copper composite material, the tensile strength of the welded joint along the rolling direction of the base material was 548 MPa.
[0057] Comparative Example 2
[0058] This example is carried out according to the method of Example 1, except that in step (1), in the first flattening process, it is divided into small units A with a size of 11.5×3.8 mm, and bent into workpieces. The remaining steps and parameters are the same as in Example 1.
[0059] Among them, a step-structured copper-molybdenum-copper-copper composite material with a width of 3.8 mm and a step height of 0.45 mm was obtained; wherein, in the step-structured copper-molybdenum-copper-copper composite material, the tensile strength of the welded joint along the rolling direction of the base material was 542 MPa.
[0060] Comparative Example 3
[0061] This example is carried out according to the method of Example 1, except that in step (1), in the first flattening process, it is divided into small units A with a size of 13.2×3.5 mm, and is bent into workpieces. The remaining steps and parameters are the same as in Example 1.
[0062] Among them, a step-structured copper-molybdenum-copper-copper composite material with a width of 13.2 mm and a step height of 0.55 mm was obtained; wherein, in the step-structured copper-molybdenum-copper-copper composite material, the tensile strength of the welded joint along the rolling direction of the base material was 538 MPa.
[0063] Comparative Example 4
[0064] This example is carried out according to the method of Example 1, except that in step (1), in the first flattening process, it is divided into small units A with a size of 12.6×3.6 mm, and is bent into workpieces. The remaining steps and parameters are the same as in Example 1.
[0065] Among them, a step-structured copper-molybdenum-copper-copper composite material with a width of 3.6 mm and a step height of 0.52 mm was obtained; wherein, in the step-structured copper-molybdenum-copper-copper composite material, the tensile strength of the welded joint along the rolling direction of the base material was 533 MPa.
[0066] Test Case
[0067] The tensile strength performance test was performed on the materials obtained in the above embodiments and comparative examples. The test method was carried out with reference to the standard "GB / T17737.308-2018 Tensile Strength and Elongation Test of Copper Clad Metals". The results are shown in Table 1.
[0068] Table 1
[0069] serial number Tensile strength(MPa) Example 1 600 Example 2 592 Example 3 595 Comparative Example 1 548 Comparative Example 2 542 Comparative Example 3 538 Comparative Example 4 533
[0070] It can be seen from the results in Table 1 that the step-structured copper-molybdenum-copper-copper composite material prepared by the method of the present invention has significantly better mechanical properties in the rolling direction.
[0071] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a step-structured copper-molybdenum-copper-copper composite material, characterized in that: The method comprises the following steps: (1) using a flat structured molybdenum material as a core material, and cladding copper plates I and II on both sides of the core material, respectively, to obtain an intermediate material having a structure of copper plate I-core material-copper plate II from top to bottom, and performing rolling treatment, first flattening treatment, and first cutting treatment on the intermediate material in sequence, to obtain an intermediate (2) having a thickness of 0.01 to 1 mm, a length of 5 to 80 mm, a width of 2 to 40 mm, and a thickness ratio of copper, molybdenum, and copper of 1:(1 to 7):1; (2) placing the oxygen-free copper sheet in a mold and sequentially performing a second flattening process, a second cutting process, and a bending process to obtain an inverted U-shaped copper sheet (1); The surfaces and butt joint surfaces of the intermediate (2) and the inverted U-shaped structure copper sheet (1) are mechanically polished step by step using 100#, 200#, 400#, 800# and 1000# sandpapers, and then ultrasonically cleaned in ethanol for 10 to 20 minutes, vacuum dried for 10 to 30 minutes, and then the two are placed side by side on a welding table, and the positions of the two are adjusted so that the butt joint surfaces of the two are in close contact, and the two interface materials are welded using a continuous laser (3), and after the metal in the molten pool (5) solidifies, the weld surface is forged using a pulsed laser (4), and then in-situ heat treatment is performed to obtain a weldment; (3) Mechanically dividing the weldment into units to obtain a copper-molybdenum-copper-copper composite material with a stepped structure.
2. The method according to claim 1, wherein: In step (1), the rolling process is to thin the thickness of the intermediate material in multiple passes, and the first pass is to thin the intermediate material to 50% of the initial thickness, the second pass is to thin the intermediate material to 30% of the initial thickness, the third pass is to thin the intermediate material to 20% of the initial thickness, and the fourth pass is to thin the intermediate material to 10% of the initial thickness, until the thickness is thinned to 0.01-1 mm, that is, the rolling process is terminated; annealing heat treatment is required each time the thickness is thinned.
3. The method according to claim 2, wherein: In step (1), the conditions for reducing the thickness of the intermediate material in multiple passes are as follows: temperature is 550-590° C., and time is 0.5-2.5 h.
4. The method according to claim 2, wherein: In step (1), the annealing heat treatment conditions are as follows: temperature is 650-850° C., and time is 0.5-2.5 h.
5. The method according to claim 1, wherein: In step (2), the welding process conditions are as follows: the power of the continuous laser (3) is 2000-6000W, the welding rate is 10-30mm / s, the shielding gas is argon, and the flow rate of the shielding gas is 10-25L / min.
6. The method according to claim 1, wherein: In step (2), the forging treatment uses a pulse spot radius of 0.2 to 0.4 mm, and the forging treatment is to start from the beginning of the weld and move horizontally along the width direction of the weld to the end of the weld, completing one cycle, and repeating three times; and the conditions of the forging treatment meet: the power density of the pulse laser (4) is 0.6 to 1.2 GW / cm 2 , the pulse width is 10 to 30 ns, the frequency is 1 to 10 kHz, the forging rate of the pulse laser (4) is 5 to 20 mm / s, the shielding gas is argon, and the shielding gas flow rate is 10 to 25 L / min.
7. The method according to claim 1, wherein: In step (2), the in-situ heat treatment conditions are as follows: the temperature is 700° C. to 850° C. and the insulation time is 30 min to 60 min.
8. The method according to claim 1, wherein: In step (1) and step (2), the first leveling treatment and the second leveling treatment are performed by using a high-precision leveling machine at room temperature for 3 to 5 times to ensure that the flatness is ≤ 0.02 mm; And / or, in step (1) or step (2), the first cutting process and the second cutting process are to cut the material by a wire cutting machine or a high-precision cutting machine to ensure that the dimensional tolerance is ±0.01 mm.
9. The method according to claim 1, wherein: In step (2), the bending process is performed by using a high-strength steel concave-convex mold. The flat plate material to be bent is laid flat in the mold groove for positioning, covered with an upper mold, and the operation is started on a punch press with a press pressure of 0.1 to 3 MPa. The mold is then removed and the bending is completed.
10. A step-structured copper-molybdenum-copper-copper composite material prepared by the method according to any one of claims 1 to 9, characterized in that: The step-structured copper-molybdenum-copper-copper composite material has a thickness of 0.02-0.08 mm, a width of 2-5 mm, and a step height of 0.1-0.55 mm.